2017
DOI: 10.1590/0103-6440201701527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reciprocating Systems and Working Lengths on Apical Microcrack Development: a micro-CT Study

Abstract: The objective of this study was to evaluate the effect of root canal preparation with single-file reciprocating systems at different working lengths on the development of apical microcracks using micro-computed tomographic (micro-CT) imaging. Forty extracted human mandibular incisors were randomly assigned to 4 groups (n=10) according to the systems and working length used to prepare the root canals: Group A - WaveOne Gold at apical foramen (AF), Group B - WaveOne Gold 1 mm short of the AF (AF-1 mm), Group C -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Under this micro-CT technology, the current study revealed that no microcrack could be attributed to root canal instrumentation with either the ProTaper Universal for Hand Use, the HyFlex EDM or the Reciproc Blue. This result agrees with previous investigations (de Oliveira et al 2017a, b, PradeepKumar et al 2019, R€ odig et al 2019) that also showed a lack of relationship between microcrack formation and biomechanical preparation with hand, rotary or reciprocating instruments by using micro-CT analysis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Under this micro-CT technology, the current study revealed that no microcrack could be attributed to root canal instrumentation with either the ProTaper Universal for Hand Use, the HyFlex EDM or the Reciproc Blue. This result agrees with previous investigations (de Oliveira et al 2017a, b, PradeepKumar et al 2019, R€ odig et al 2019) that also showed a lack of relationship between microcrack formation and biomechanical preparation with hand, rotary or reciprocating instruments by using micro-CT analysis.…”
Section: Discussionsupporting
confidence: 93%
“…These conflicting findings reported in micro-CT studies can be related to different methodological approaches used. Some of these are as follows: scanning and reconstruction parameters, interpretation of defects and digital artefacts, number of cross-sectional images assessed and, mainly, the conditions of samples storage (Versiani et al 2015, de Oliveira et al 2017a, R€ odig et al 2019. Concern has been raised that dehydration of extracted teeth may induce spontaneous cracking or may affect the biomechanical response of root dentine to instrumentation, and so, decrease teeth resistance to the fracture (Versiani et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations